Design and Operating Characteristics of Heat Storage Device for Annular Unit - Hou Pumin; Mao Jinfeng; Liu Rongrong; Chen Fei (Zhileng xuebao)
Experiments were carried out to study the thermal performance of cylindrical and annular units. The results show that the annular structure effectively reduces the heat storage time and improves the heat storage rate of phase change materials. A novel phase change heat storage device is designed using annular units, and a phase change heat storage experiment system is set up to analyze the operation characteristics of the heat storage device. The results show that the rate of heat transfer is significantly improved when the flow rate and temperature of the heat transfer fluid increase. Under the discharge conditions, the rate of heat transfer is significantly improved when the flow rate of the cold fluid increases within a reasonable range. The heat storage device provides more than 44 L of hot water at a cold water flow rate of 4 L/min. According to the water usage conditions, the performance that water was supplied intermittently every 5 min and 10 min were investigated experimentally, and the results show that the water demand could be satisfied.